Low‐ and lower middle‐income countries advanced practice nurses: an integrative review. (31st July 2019) - Scanlon, A.; Murphy, M.; Smolowitz, J.; Lewis, V.
Abstract : Aim: To review published literature descriptions of advanced practice nurses' roles in low‐ and lower middle‐income countries. Background: Advanced practice nurse roles have the potential to address insufficient healthcare resources in low‐ and lower middle‐income countries. Introduction: This integrative review highlights advanced practice nurses' roles in the delivery of healthcare services in low‐ and lower middle‐income countries. Methods: Three electronic databases PubMed, CINAHL complete and ProQuest Health & Medicine were searched. No limits by year or language were set. The names for low‐ and lower middle‐income countries and combinations 'related to advanced practice nurses' titles were used to identify papers. In addition, a review of publication type was performed. Themes found within the publications were assessed against the advanced practice nurses' International Council of Nurses' characteristics. An integrative review facilitated an appraisal of the papers identified. Results: The initial search identified 5778 publications in 16 languages. This number was reduced to 23, from 18 low‐ and lower middle‐income once exclusion criteria were applied. Six publications were from 1977 to 1999, and six between 2000 and 2010, with the remaining 11 from 2011 to 2018. Zambia had the most publications. Notably, 63 countries were not represented. Of those meeting inclusion criteria, the majority addressed education with a lesser extent focusing on practice and regulation of advanced practice nurse's roles. The majority were published during the last decade. Discussion: This review of the published literature identified advanced practice nurses' roles and function within some healthcare systems. However, not all components were reported. Examination of the grey literature could provide additional information about the actual and potential benefits of advanced practice nurses' in low‐ and lower middle‐income countries. Conclusion: The published literature that referred to advanced practice nurses' identified their contribution to positive impacts on health care over the last 40 years. However, with only 11 publications identified in the last 7 years, further review is required to understand the advanced practice nurses' roles in these countries. Implications for nursing and/or health policy: Further development of advanced practice nurses' in low‐ and lower middle‐income countries is supported by the lack of published literature.